Numerical Experimentation to obtain the Scaling Laws of Mather type Dense Plasma Focus machines working in Argon gas - Arwinder, Singh*; Saw, Sor Heoh; Lee, Sing* (INTI International University, 2020)
In this paper, a total of 5 Dense Plasma Focus (DPF) machines, working in argon gas which uses Mather type anode (7 energy range), were analysed using numerical experimentation (Lee Codes). Three important scaling laws relating the all line yield to the peak current, pinch current and energy input into the plasma were obtained. The scaling laws act as guidelines in scaling the DPF for applications such as medical radiation.